Development of pseudo interface element for modelling of reinforced brick masonry - Mehendale, Shashank Vasudeo; Bambole, Abhay Namdev; Raghunath, S (Revista ALCONPAT, 2017)
Strength of reinforced masonry is influenced by interfaces between brick, mortar and reinforcement. Experimental protocol has been defined to characterise the behaviour of reinforced brick masonry joint, with reinforcement steel embedded in cement mortar 1:6. This is applicable for low-strength, low-stiffness brick masonry found. Experimental investigations show that bond between masonry and steel is not perfect. Considering critical bond mechanisms, an attempt is made to put-forth a novel approach for development of a pseudo interface element representing three different materials (viz. brick, mortar and reinforcement) and two interfaces (reinforcement-mortar (RM) interface and brick-mortar (BM) interface). Principles of classical Reinforced Concrete (RC) design can therefore be directly applied to reinforced masonry with the introduction of the proposed pseudo interface element.